Role of Transition Metal in Fast Oxidation Reaction on the Pt3TM (111) (TM = Ni, Co) Surfaces. Issue 10 (29th May 2013) - Kim, Yong Su; Jeon, Sang Ho; Bostwick, Aaron; Rotenberg, Eli; Ross, Philip N.; Stamenkovic, Vojislav R.; Markovic, Nenad M.; Noh, Tae Won; Han, Seungwu; Mun, Bongjin Simon
<x xml:space="preserve">Abstract</x> Revealing the electronic structures of Pt‐alloys explains why the addition of transition metal to Pt speeds up the oxygen reduction reaction. It is found that transition metals in the subsurface induce charge polarization at the surface and suppresses the surface‐states. The modified surface‐states of Pt surface layer critically affects the chemical bonding between oxygen and Pt surfaces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>